MIGRANT WORKERS FROM CENTRAL ASIAN COUNTRIES ON THE RUSSIAN LABOR MARKET: LIVING CONDITIONS AND SELF-PRESERVING BEHAVIOR - IVANOVA, Alla; RYAZANTSEV, Sergey (CENTRAL ASIA AND THE CAUCASUS, 2017)
Work migrants fall into the category of vulnerable groups in the host society, a fact that is stipulated by a wide range of risk factors on one side and obstacles in obtaining medical and social assistance on the other. Thus, the danger of spreading public health hazards within migrant groups in host societies is growing, which may, according to certain experts, pose a problem to the society as a whole. The goal of this research is to determine the tenability of concerns regarding the substantial threat of spreading public health hazards among Central Asian work migrants in Russia. A total of 498 work migrants, citizens of Central Asian states, were polled in Moscow. The social and demographic makeup of the respondents largely coincides with that of similar groups examined by other authors, allowing us to consider our results on health status and self-preserving behavior representative of this population group in major Russian cities. The results attest to the fact that the main health risks, aside from professional ones, lie with the work migrants’ living conditions and the nature of their diet, which is characterized by a high intake of low-quality meat products and a low intake of dairy products, fruits, and vegetables. This dietary pattern is directly linked to the risk of diabetes mellitus and cardiovascular disease, which is increased by family anamnesis and a lack of information on risk prevention. While the frequency of sexual contacts is relatively high, only under 50% of the respondents use any means of protection. Over one third of the men and over one half of the women with more than one sexual partner practice unprotected sex, which may lead to the spread of sexually transmitted diseases. Meanwhile, work migrants intend to seek medical aid in case of illness, particularly if they possess Mandatory Medical Insurance. Regardless of the motives that prioritize a visit to a medical institution over other methods of “fighting the disease,” these results are significant for improving the epidemiological situation in the regions that actively attract work migrants from Central Asia.